EKSTRAKSI GLUKOMANAN DARI UMBI PORANG (Amorphophallus paeniifolius (Dennst.) Nicolson) - Elis Setiawati; Syaiful Bahri; Abd. Rahman Razak (Chemistry Department, Mathematics and Natural Science Faculty, Tadulako University, 2017)
This study aims to determine the temperature and the ratio of tuber flour porang using isopropyl alcohol precipitator in producing glucomannan extract with the highest yield. The study was designed using completely randomized design (CRD), which consists of two factors: the temperature of the extraction consists of seven levels (45, 55, 65, 75, 85, 95, and 105 0C) and the ratio of tuber flour porang by precipitating isopropyl alcohol consists of 5 level (1: 7, 1:10, 1:13, 1:16, and 1:19 (w/v). each done in duplicate. parameters measured were yield characteristics glucomannan and the results showed that the extraction of the best glucomannan obtained at a temperature of 95 0C with a yield of 41.614%. the ratio of starch tuber porang best isopropyl alcohol is 1:19 (w/v) with a yield of 45.167% glucomannan. Test characteristics of glucomannan gained 6.6% moisture content, the ash content of 0.8%, and a molecular weight of 0.726 x 104 g/mol.Keywords: porang tuber flour, shaking temperature, glucomannan.